Abstract: This article is about the peculiarities of the development of social and cultural education among schoolchildren by means of theatrical performances based on folk tales, which contributes to the development of children’s interest, love for books - Akhmedova Aziza Khusenovna (International Engineering Journal For Research & Development, 2022)
This article discusses the process of formation of semantic neologisms as one of the ways to replenish the vocabulary of the modern Russian language. In the article, the world Wide Web is considered as a special medium for communication, a special place for the implementation of language, a means of communication and information exchange among the younger generation, as a result of which the semantics of lexical units used in it undergoes changes, sometimes very significant. Neologisms actively used in social networks in recent decades were considered as the object of study.